PERAN PEMIMPIN TRANFORMASIONAL UNTUK MENCAPAI KEUNGGULAN BERSAING DALAM PERUSAHAAN - Muallifah., MA (El-QUDWAH, 2013)
PERAN PEMIMPIN TRANFORMASIONAL UNTUK MENCAPAI KEUNGGULAN BERSAING DALAM PERUSAHAAN Oleh: Muallifah Fakultas Psikologi UIN Maulana Malik Ibrahim Malang Jl. Gajayana No. 50, Malang Email: aliefaha@gmail.com Abstract Discussing business we could not forget two popular terms, change and competition, because one of the condition of successful corporation always need change and transformation. Besides, there are many competitions outside made corporation needs great strategies to pass and win competition. One of these is leadership style. Nowdays, for global change of corporation, transformation, generate organization or corporate effectiveness we need a transformational leadership style. This article reviews the competitive advantage and the role of transformational leadership. Keywords: Transformational leadership, competitive advantage.